Calculus of variations mechanics, control, and other applications - MacCluer, Charles (Pearson/Prentice Hall, 2005)
This is the first truly up-to-date treatment of calculus of variations - and the first to incorporate a simple introduction to key concepts such as optimization, optimal control, bang-bang, Pontryagin's maximum principle, or LQ control design. Introduces all material using simple, easily understood applications that are worked and reprised several times throughout. Features a large number of exercises, ranging widely in difficulty. Gives readers a broader, "big picture" perspective that makes the material less overwhelming. Offers a useful, stand-alone discussion of MATLAB ("MATLAB Cookbook") in the appendices. Includes a clear introduction to weak/strong sufficiency. A useful reference for engineers, chemists, and forest/environmental managers.